Development and Validation of the Agency for Healthcare Research and Quality Measures of Potentially Preventable Emergency Department (ED) Visits: The ED Prevention Quality Indicators for General Health Conditions. (30th March 2017) - Davies, Sheryl; Schultz, Ellen; Raven, Maria; Wang, Nancy Ewen; Stocks, Carol L.; Delgado, Mucio Kit; McDonald, Kathryn M.
Abstract : Objective: To develop and validate rates of potentially preventable emergency department (ED) visits as indicators of community health. Data Sources: Agency for Healthcare Research and Quality, Healthcare Cost and Utilization Project 2008–2010 State Inpatient Databases and State Emergency Department Databases. Study Design: Empirical analyses and structured panel reviews. Methods: Panels of 14–17 clinicians and end users evaluated a set of ED Prevention Quality Indicators (PQIs) using a Modified Delphi process. Empirical analyses included assessing variation in ED PQI rates across counties and sensitivity of those rates to county‐level poverty, uninsurance, and density of primary care physicians (PCPs). Principal Findings: ED PQI rates varied widely across U.S. communities. Indicator rates were significantly associated with county‐level poverty, median income, Medicaid insurance, and levels of uninsurance. A few indicators were significantly associated with PCP density, with higher rates in areas with greater density. A clinical and an end‐user panel separately rated the indicators as having strong face validity for most uses evaluated. Conclusions: The ED PQIs have undergone initial validation as indicators of community health with potential for use in public reporting, population health improvement, and research.